Improving The Students’ Speaking Ability by Using Small Group Discussions at The Eighth Grade of SMP Swasta Idanoi - Telaumbanua, Melisandi; Laoli, Adieli; Waruwu, Yaredi; Harefa, Afore Tahir (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This study seeks to enhance students’ speaking abilities through small group discussions. Many students face challenges in speaking English due to a lack of confidence and practice, while teachers often overlook engaging strategies that motivate students to participate. To address this, the researcher employed Classroom Action Research (CAR), which consisted of two cycles, each comprising two meetings focused on planning, action, observation, and reflection. Data were collected through observations, field notes, and evaluation sheets. The findings revealed significant improvement in each cycle, thanks to the grouping technique. In the first cycle, the average student score was 51, with many students not meeting the minimum competency standards (KKM). By the second cycle, however, all students successfully passed, achieving an average score of 79. The researcher concluded that small group discussions are an effective way to boost students’ speaking ability. It is recommended that both students and teachers adopt this technique to further improve their speaking abilities.